A new magnetic observatory in La Réunion Island – meeting data quality requirements in a volcanic island setting - Heumez, Benoit; Pesquiera, Frédérick; Telali, Abdelkader; Lesur, Vincent (Geoscientific instrumentation, methods and data systems, 2025)
A new magnetic observatory has been set on La Réunion Island in the Indian Ocean through a collaboration between the “Institut de physique du globe de Paris” (IPGP) local volcano observatory (Observatoire Volcanologique du Piton de la Fournaise – OVPF) and its magnetic observatory service. This observatory is isolated and serves to monitor the evolution of the Earth's magnetic field in that region. It is also particularly useful for large-scale modelling of the core field and other contributions to the geomagnetic field. Three-component vector magnetic field data are continuously collected at 1 Hz using a fluxgate, while scalar data are collected at 0.2 Hz with a proton magnetometer. The data are transmitted every 5 min to IPGP main site and made immediately available to the scientific community (see http://www.bcmt.fr, last access: 22 August 2025). Due to the strong magnetic field generated by the surrounding volcanic rocks, the differences between the magnetic field strengths as recorded by the proton magnetometer and the strengths calculated from the recorded vector field values vary by more than ∼2 nT during a day. To circumvent this difficulty, constant offset values of −2400, 280, and −20 nT are added to the X, Y, and Z magnetic field components respectively, prior to the data distribution. We show that this approach efficiently reduces the differences between measured and calculated magnetic field strengths inside a day. Calibrated observatory data have been calculated over the year 2023, and, although the baseline values present variations up to 70 nT throughout that year, the derived data meet the quality required for an intermagnet observatory. A Fourier analysis of the data shows that these are not contaminated by significant noise even if peaks at 0.2 Hz indicate small cross-talk between vector and scalar instruments.